Intergrasi Algoritma Clustering K-Means dan Simulasi Stokastik untuk Pemetaan dan Prediksi Peningkatan Kualitas Layanan Rehabilitasi (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
The disparity in the quality of rehabilitation services across regional work units presents a significant challenge to effective public management. This study aims to bridge the gap between problem diagnosis and policy prediction by proposing a hybrid, data-driven approach. We integrate K-Means Clustering to map the current state of service quality and Stochastic Simulation to predict the impact of strategic interventions. Using the 2024 Public Satisfaction Index (IKM) dataset from the National Narcotics Agency (BNN), the K-Means algorithm initially identified 26 work units (15.7%) in the